A methodology for the electrical characterization of shaded high concentrator photovoltaic modules. (September 2015) - Rodrigo, P.; Gutiérrez, S.; Velázquez, Ramiro; Fernández, Eduardo F.; Almonacid, F.; Pérez-Higueras, P.J.
Abstract: In this paper, a methodology for characterizing the I–V curve of partially shaded high concentrator photovoltaic modules is presented. It takes into account atmospheric parameters (direct normal irradiance, ambient temperature, wind speed and air mass) as well as the amount of shading on each receiver lens and the module electrical configuration. Two high concentrator photovoltaic modules have been characterized in order to apply the methodology. Both modules have been measured under different shading conditions and a comparison between experimental and simulated behavior has been carried out. It was found root mean squared errors for the I–V curves lower than 4% and absolute values of relative errors at the maximum power point lower than 3% in 80% of the analyzed measurements. The methodology can be regarded as a step for the development of a complete model for the electrical characterization of shaded high concentrator photovoltaic power plants. Highlights: Methodology for characterizing the I–V curve of shaded HCPV modules. It uses as inputs atmospheric parameters and shading factors of the lenses. Experimental curves were compared to simulated curves. RMSE lower than 4% in 80% of the measurements was obtained.